IMPLEMENTASI MARKERLESS AUGMENTED REALITY PADA APLIKASI PENGENALAN ALAT OLAHRAGA HOCKEY MENGGUNAKAN METODE USER DEFINED TARGET BERBASIS ANDROID - Kadek Dwi Nuryana , I; Zuyyinal Haqqul Barir , Much.; Ikhwan Muhammad , Zainal (Inovate, 2023)
Hockey is one of the sports that has been played in Indonesia, but this sport is still not popular enough and hockey sports equipment is also rarely found in sports shops in general, for that it is necessary to introduce hockey so that people are interested in starting to play the sport this. One way to introduce this sport is to utilize augmented reality technology so that people can get to know this sport efficiently and flexibly. One method for displaying augmented reality objects is using markerless with user defined target techniques. In the application, accuracy testing is carried out using distance, light intensity and the target to be used as a marker. As for the results of testing at an angle, applications can display 3D objects on dark targets with contrast using a minimum reading angle of 0° and a maximum of 45° and light targets with contrast with a minimum reading angle of 0° and a maximum of 45°. In testing the distance, the application is able to display 3D objects against dark targets with contrast at a distance of 50 cm to 70 cm and bright targets with contrast at a distance of 50 cm to 70 cm. In testing light intensity, the application can display 3D objects on dark targets with contrast when the light intensity is at a minimum of 70 lux and a maximum of 1000 lux and on bright targets with contrast when the light intensity is at least 70 lux and a maximum of 1000 lux. Based on the results of the questionnaire, it was found that this application was very feasible with a value of 88%. Keywords : Hockey, Sports Equipment, Augmented Reality, Markerless.